Relationship Between Tumor Infiltrating Lymphocytes (TIL) With Histopathological Grading, Tumor Size, and Axillary Lymph Node Metastases in Breast Cancer at the Anatomical Pathology Laboratory of Soedarso Hospital Pontianak - Damayanti, Renita; Trianto, Heru Fajar; Pratiwi, Sari Eka; Suhardiman, Eko Rustianto; Fitrianingrum, Iit (Indonesian Journal of Cancer, 2025)
Background: Breast cancer has a high prevalence rate, with diagnosis often occurring at an advanced stage (stage III-IV), particularly in developing countries. Tumor-infiltrating lymphocytes (TILs) are a prognostic factor that can be assessed based on histopathological features in relation to response to therapy. Furthermore, histopathological grading, tumor size, and lymph node metastasis are predictive factors for breast cancer prognosis. This study aimed to investigate the relationship between TIL and other predictive factors, histopathological grading, tumor size, and axillary lymph node metastasis.Methods: This research is an observational analytic study with a cross-sectional approach. This research was approached by observing the 55 tissue slides of hematoxylin-eosin (HE) in breast cancer patients that met the inclusion and exclusion criteria. The inclusion criteria included breast cancer patients who underwent histopathological examination at the Anatomical Pathology Laboratory of Dr. Soedarso Hospital Pontianak in the period January until December 2021 with invasive carcinoma of no special type and had undergone Modified Radical Mastectomy (MRM) surgery. The exclusion criteria were patients with breast cancer recurrence and double primary cancer cases, and no data on tumor size was obtained on the results of histopathological examination. The data collected was then statistically analyzed with the Spearman test. Results: Breast cancer in this study was mostly diagnosed as grade III, T4, and N2. The results of the Spearman's rho correlation test showed that there was no correlation between TIL and the histopathological grading (p = 0.231; r = 0.164 ), tumor size (p = 0.507; r = -0.091), and axillary lymph node metastases (p = 0.842; r = -0.028).Conclusions: There is no statistically significant correlation between TIL and the grade, tumor size, and axillary lymph node metastases in breast cancer at the anatomical pathology laboratory of Soedarso Hospital Pontianak.